Intradural Extramedullary Capillary Hemangioma in the Upper Thoracic Spine: A Review of the Literature - Yoichiro Takata; Toshinori Sakai; Kosaku Higashino; Yuichiro Goda; Fumitake Tezuka; Koichi Sairyo (Case Reports in Orthopedics)
Capillary hemangiomas are benign tumors found in the skin and soft tissues in younger people. They occur in the central nervous system only rarely, and intradural occurrence is extremely rare. We report here a 60-year-old man presenting with thoracic girdle pain and progressive gait disturbance. Magnetic resonance images of the thoracic spine showed a 12×8×20 mm, well-defined intradural mass at the T2 level, compressing the spinal cord laterally. Relative to the spinal cord, the mass was hypo- to isointense on T1-weighted images and relatively hyperintense on T2-weighted images, with strong enhancement on contrast-enhanced T1-weighted images. The patient underwent T1-2 hemilaminectomy with resection of the intradural extramedullary tumor, which showed characteristics of a capillary hemangioma on histologic examination. The patient’s symptoms improved following the surgery and no clinical or radiological evidence of recurrence was noted at the 2-year follow-up. We present this case with a review of the literature, highlighting features for differential diagnosis.